(untitled) (BIRDEM Medical Journal, 2013)
Solid pseudopapillary tumor of pancreas is a rare tumor almost exclusively affecting the young female and accounts for <1% of all pancreatic tumors. Most hypothesis suggests that the tumor arises from embryonic pleuripotent stem cells. Although mostly benign in nature, the tumor may show malignant potentials and the patient may present with hepatic, omental or other meatstasis. High index of suspicion is the key for early dianosis. Good quality imaging (USG and CT scan) & FNAC are necessary for proper evaluation of the lesion. Peroperative frozen section biopsy may be necessary to ascertain its malignant potential. Radical resection is the best modality of treatment for achieving curative results and a better long-term survival. We are reporting our experience of treating a case of solid pseudopapillary tumor of pancreas in BIRDEM Hospital. Birdem Med J 2013; 3(1): 54-58 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17129